Health promotion via SMS improves hypertension knowledge for deaf South Africans - Hanne Jensen Haricharan; Marion Heap; Damian Hacking; Yan Kwan Lau (BMC, 2017)
Abstract Background Signing Deaf South Africans have limited access to health information. As a result, their knowledge about health is limited. Cell phone usage in South Africa is high. This study aimed to assess whether a short message service (SMS)-based health promotion campaign could improve Deaf people's knowledge of hypertension and healthy living. Additionally, the study aimed to assess the acceptability of using SMSs for health promotion targeting Deaf people. Methods A baseline questionnaire assessed participants' knowledge about hypertension before an SMS-based information campaign was conducted. After the campaign, an exit questionnaire was conducted, containing the same questions as the baseline questionnaire with additional questions about general acceptability and communication preferences. Results were compared between baseline and exit, using McNemar's test, paired t-test and Wilcoxon signed-rank test. Focus groups aimed to get further information on the impact and acceptability of SMSs. The focus groups were analysed using inductive thematic analysis. Results The campaign recruited 82 participants for the baseline survey, but due to significant loss-to-follow-up and exclusions only 41 participants were included in the analysis of the survey. The majority (60%) were men. Eighty percent were employed, while 98% had not finished high school. The campaign showed a statistically significant improvement in overall knowledge about hypertension and healthy living amongst participants. Six individual questions out of 19 also showed a statistically significant improvement. Despite this, participants in focus groups found the medical terminology difficult to understand. Several ways of improving SMS campaigns for the Deaf were identified. These included using using pictures, using 'signed' SMSs, combining SMSs with signed drama and linking SMS-campaigns to an interactive communication service that would enable the Deaf to pose questions for clarification. Focus groups suggested that participants who were hypertensive during the campaign adopted a healthier lifestyle. Conclusion SMSs were effective in improving Deaf people's knowledge of hypertension and healthy living. However, SMS-campaigns should be cognizant of Deaf people's unique needs and communication preference and explore how to accommodate these. Trial registration The research was registered with the Pan African Clinical Trial Registry on December 1, 2015. Identification number: PACTR201512001353476 .